L'adverbi totavia al Curial e Güelfa: un possible italianisme lèxic. - ANTOLÍ MARTÍNEZ, JORDI (Scripta)
The adverb totavia is a singular word in the language of the Curial e Güelfa, both because of its frequency and because of the values it presents in the work. This has already been observed in several previous studies, which have considered this exceptionality as a result of interference from French or Italian, or which have qualified it as cultism. In this study, we intend to analyse the use of the word in the novel and to formulate a hypothesis about its singularity. To do so, we will characterise the adverb semantically and functionally in Old Catalan, with a diachronic perspective (12th-16th century), and we will contrast the results obtained with those of the Curial e Güelfa. On the other hand, and taking as a basis several studies on the derivatives of TOTA VIA in French, Italian and Spanish, we will compare the results obtained with the data on these adverbs in the 15th century. In this study, we conclude that the characterisation of the word in the Curial e Güelfa does not correspond to that of totavia in Old Catalan nor to that of the French parallel; it is closer to the characterisation of the adverb in contemporary Spanish and, above all, to that of the Italian tuttavia. We conclude, therefore, that we are dealing with a -possible- new semantic Italianism.